(untitled) (Current Horticulture, 2024)
This field experiment was laid out by adopting F test at farmers’ fields of marigold (Tagetes species Linn.) at Mutkod and Kellur village of Jewargi taluk during 2018-19. Totally 3 treatments were considered by three different varieties, Arka Agni and Arka Bangara 2 from IIHR, Bengaluru and local variety from Jewargi. The mean value of plant height was highest in Arka Agni (40.16 cm), followed by local variety (35.6 cm) Arka Bangara 2(33.6 cm). The variation in plant height due to genotypic differences in phenotypic expression of plant height is due to genotype-environmental interaction effects on plant height.